Epidemiological aspects of cystic echinococcosis in slaughtered herbivores in Sari abattoir, North of Iran - Ziaei, Hajar (Springer-Verlag, 2011)
A study was conducted to assess the ruminants’ hydatidosis in Mazandaran Province, Northern Iran. A total, 1,799 sheep, 985 goats and 362 cattle slaughtered at Sari industrial slaughter house were examined for hydatid cyst infection. The results indicated that 65.2% of sheep, 37.8% of goats and 40.1% of cattle were infected. The liver and lung infection rate in sheep were 18.8 and 4.3%, goats 17.2 and 12.6% and cattle 44.1 and 7.6%, respectively. The study showed that 766 (45.3%) out of 1,691 infected animals had moderate degree of infection. Geographical zone survey indicated that 1,381 (89.2%) out of 1,546 sheep and goats infected with hydatid cyst were non-indigenous and originated from north-eastern provinces of Iran. On the contrary, 50.3% of infected cattle originated from Mazandaran Province (indigenous).